Plagiarisme Digital Mahasiswa PPKn Kelas 41 sebagai Krisis Nilai Kemanusiaan dalam Perspektif Pancasila Era AI - Hidayat, Maulana Fathir; Mrr Ratna Endang Widuatie; Raihan Fakhruddin Al Zadid; Rismay Viantika Martha Putri; Rania Syahda Awandini; Sarah Putri Aulia (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The phenomenon of digital plagiarism has become increasingly alarming among university students, especially in the era of the Artificial Intelligence (AI) Revolution that emphasizes speed and efficiency. This study aims to identify the forms, causes, and impacts of digital plagiarism among students of the General Education Course Pancasila 41, and to analyze the emerging crisis of human values from the perspective of Pancasila. A qualitative approach was combined with an online survey using Google Form, involving 30 student respondents. The results indicate that most students regularly use AI technologies such as ChatGPT and other content generators for academic purposes. Although AI facilitates efficiency in completing assignments, several students admitted a decline in academic honesty and ethical awareness. This phenomenon illustrates a crisis of human values particularly honesty, responsibility, and respect for intellectual property which reflect the second and fifth principles of Pancasila. The study highlights the urgency of developing Pancasila-based digital ethics literacy to cultivate morally responsible students amid the rapid growth of AI technology.